Judicial Policy and Institutional Efficiency in the Lima Superior Court of Justice: The Liquidation of the 1940 Code of Criminal Procedure - Noronha Val, Diego Alonso (2026)
This article examines the liquidation of criminal cases processed under Peru’s 1940 Code of Criminal Procedure as the unfinished core of criminal procedure reform. Using a systematic review of specialized literature from Latin America (SCOPUS, PROQUEST and CEJA), it identifies three qualitative studies on procedural reforms and reconstructs shared structural challenges: a persistent bureaucratic–inquisitorial legal culture, disordered coexistence between the old written system and the new accusatory model, and chronic deficits in strategic management and modern judicial administration tools. When contrasted with the current situation of the Lima Superior Court, the evidence reveals the lack of a designated liquidation authority, specialized courts, clear transitional jurisdictional rules, and effective mechanisms for inactive cases. The study argues that completing liquidation is an implicit yet essential institutional objective to achieve constitutional and conventional efficiency, ensure equal access to justice, and fully consolidate the accusatory criminal procedure system.